ANALISIS MOTIVASI DAN MINAT BELAJAR SISWA DALAM MODEL DISCOVERY LEARNING - Pramudika, Fernandi; Susilo, Claudya Zahrani (IJPSE Indonesian Journal of Primary Science Education, 2024)
Today's learning activities are becoming increasingly complex, along with the progress of the times and changes in the education process in the modern era, it cannot be separated from its influence on the condition of student motivation and interest in learning activities. Elementary school students can foster good motivation and interest in learning through good and active learning activities. Motivation and interest in learning are the initial capital that students must have in learning. The purpose of fostering motivation and interest in learning is basically to improve students' cognitive, affective, and psychomotor abilities. This study aims to analyze students' motivation and interest in learning in the discovery learning model in class III SDN Jombatan 3 Jombang. This research was conducted on mathematics learning material on fraction reduction. This research used a qualitative approach with a case study method. The case study was conducted by in-depth exploration related to the condition of motivation and interest in learning of grade III students in discovery learning conducted within a certain period of time. Data collection techniques included interviews, observations and documentation related to the condition of students' motivation and interest in learning in the discovery learning model. The results of this study found that there are factors that influence the condition of students' motivation and interest in learning, among others; (1) external factors: the role of the teacher, learning model, learning environment. (2) Internal factors: student intelligence, student study habits, and student health.